The loss and damage fund as a site of global resistance: Power asymmetries and normative disruption in climate governance - Abdul Halim; Sari Mutiara Aisyah; Erlisa Saraswaty; Roy Setiawan; Sri Mulya Pratiwi; Athira Nisrina; Wahyu Saputra (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
The issue of loss and damage has long been sidelined in global climate governance, despite its increasing urgency for climate-vulnerable countries. This study examines the political, moral, and cultural dimensions of climate justice that shaped the negotiation and institutionalization of the Loss and Damage Fund (LDF) under the UNFCCC framework. Politically, the fund reflects enduring power asymmetries between developed and developing countries; morally, it embodies contested claims of historical responsibility; and culturally, it signals a shift in global norms toward reparative justice and transnational solidarity. Using a qualitative-descriptive approach, the research draws on official UNFCCC documents, COP decisions, and academic literature to trace the institutional dynamics and strategic negotiations that enabled the fund’s creation. The findings show that Global South actors, despite internal asymmetries, strategically reframed loss and damage from a technical concern into a moral and political demand. Indonesia’s diplomatic role within the G77 coalition at COP27 illustrates how procedural resistance and discursive realignment contributed to political recognition of irreversible climate harm. This study addresses a gap in the literature by moving beyond normative appeals to examine the institutional mechanisms and strategic agency that transformed a marginalized agenda into formal policy. Its academic contribution lies in synthesizing historical institutionalism and Global South dependency theory, while connecting institutional change to broader shifts in values, norms, and global solidarity. The Loss and Damage Fund is not merely a financial instrument; it is a contested site of political struggle and symbolic transformation in the architecture of global climate governance.   Isu kerugian dan kerusakan telah lama terpinggirkan dalam tata kelola iklim global, meskipun urgensinya semakin meningkat bagi negara-negara yang rentan terhadap dampak iklim. Studi ini menelusuri dimensi politik, moral, dan kultural dari keadilan iklim yang membentuk proses negosiasi dan pelembagaan Dana Kerugian dan Kerusakan (Loss and Damage Fund/LDF) di bawah kerangka UNFCCC. Secara politik, LDF mencerminkan ketimpangan kekuasaan antara negara maju dan berkembang; secara moral, ia memuat klaim tanggung jawab historis yang diperdebatkan; dan secara kultural, ia menandai pergeseran norma global menuju keadilan reparatif dan solidaritas transnasional. Dengan pendekatan kualitatif-deskriptif, penelitian ini mengandalkan analisis dokumen resmi UNFCCC, keputusan COP, dan literatur akademik untuk menelusuri dinamika institusional dan strategi negosiasi yang memungkinkan pembentukan LDF. Temuan menunjukkan bahwa aktor-aktor Global South, meskipun memiliki asimetri internal. secara strategis mereformulasi isu kerugian dan kerusakan dari persoalan teknis menjadi tuntutan moral dan politik. Peran diplomatik Indonesia dalam koalisi G77 pada COP27 menjadi contoh bagaimana resistensi prosedural dan pergeseran wacana berhasil mendorong pengakuan politik atas kerugian iklim yang tidak dapat diadaptasi. Studi ini mengisi celah dalam literatur yang selama ini cenderung menekankan aspek normatif tanpa mengkaji mekanisme institusional dan strategi politik yang memungkinkan agenda terpinggirkan menjadi kebijakan global. Kontribusi akademik penelitian ini terletak pada sintesis teoritis antara institusionalisme historis dan teori ketergantungan Global South, serta analisis transformasi nilai dan solidaritas global. LDF bukan sekadar instrumen finansial, melainkan arena perjuangan politik dan simbol transisi kelembagaan dalam arsitektur tata kelola iklim dunia.